Ultrastructural characters of the spermatozoon of the cestode Corallobothrium solidum Fritsch, 1886 (Cestoda: Proteocephalidea), a parasite of the electric catfish Malapterurus electricus - Brunanská, Magdaléna; Scholz, Tomás; Ibraheem, Mohammed Hassan (Parasitology research, 2004)
The fine structure of the mature spermatozoon of the corallobothriine tapeworm Corallobothrium solidum Fritsch, 1886 (Cestoda: Proteocephalidea) from the electric catfish Malapterurus electricus from the Nile River in Egypt was studied by transmission electron microscopy for the first time. The filiform spermatozoon of C. solidum contains two axonemes of unequal length and a typical 9 + "1" trepaxonematan pattern. A single helicoidal crested body (30-200 nm thick) is localized at the anterior extremity of the gamete. The cortical microtubules line the periphery of the cell, largely parallel to the long axis of the spermatozoon and exhibiting signs of twisting at the beginning of region II. The nucleus, in the form of an electron-dense (largely in gametes of testes) and/or fibrous cord (largely in gametes from male reproductive ducts and seminal vesicle), coils in a spiral through the middle part (region III) of the spermatozoon. The cytoplasm contains electron-dense granules in regions II, III and partly in region IV. The cytoplasm of some spermatozoa exhibits an apparently higher electron-density at the end of the nucleated region (III), and continuously toward the middle part of region IV. The anterior and posterior extremities of the spermatozoa have a single axoneme. The ultrastructural features of the mature spermatozoon of C. solidum mostly coincide with those of the spermatozoon of other proteocephalideans, especially the gangesiine Electrotaenia malopteruri parasitizing the same host.
Keywords: Cestoda; transmisní elektronová mikroskopie; spermie; Catfishes; Spermatozoa; Male; Fish Diseases; Animals; mužské pohlaví; sumci; cestodózy; Microscopy, Electron, Transmission; Cestode Infections; zvířata; nemoci ryb